Grape pomace extract induced beige cells in white adipose tissue from rats and in 3T3-L1 adipocytes - Rodriguez Lanzi, Maria Cecilia (2018)
This study investigated the effects of a grape pomace extract (GPE) rich in phenolic compounds on brown-like adipocyte induction and adiposity in spontaneously hypertensive (SHR) and control normotensive Wistar–Kyoto (WKY) rats fed a high-fat diet (HFD). HFD consumption for 10 weeks significantly increased epididymal white adipose tissue (eWAT) in WKY but not in SHR rats. Supplementation with GPE (300 mg/kg body weight/day) reduced adipocyte diameter and increased levels of proteins that participate in adipogenesis and angiogenesis, i.e., peroxisome-proliferator activated receptor gamma (PPARγ), vascular endothelial grow factor-A (VEGF-A) and its receptor 2 (VEGF-R2), and partially increased the uncoupling protein 1 (UCP-1) in WKY. In both strains, GPE attenuated adipose inflammation. In eWAT from SHR, GPE increased the expression of proteins involved in adipose tissue “browning,” i.e., PPARγ-coactivator-1α (PGC-1α), PPARγ PR domain containing 16 (PRDM16) and UCP-1. In primary cultures of SHR adipocytes, GPE-induced UCP-1 up-regulation was dependent on p38 and ERK activation. Accordingly, in 3T3-L1 adipocytes treated with palmitate, the addition of GPE (30 μM) activated the β-adrenergic signaling cascade (PKA, AMPK, p38, ERK). This led to the associated up-regulation of proteins involved in mitochondrial biogenesis (PGC-1α PPARγ PRDM16 and UCP-1) and fatty acid oxidation (ATGL). These effects were similar to those exerted by (−)-epicatechin and quercetin, major phenolic compounds in GPE. Overall, in HFD-fed rats, supplementation with GPE promoted brown-like cell formation in eWAT and diminished adipose dysfunction. Thus, winemaking residues, rich in bioactive compounds, could be useful to mitigate the adverse effects of HFD-induced adipose dysfunction.